Dietary Vitamin E and/or Hydroxytyrosol Supplementation to Sows during Late Pregnancy and Lactation Modifies the Lipid Composition of Colostrum and Milk - Hernan D. Laviano; Gerardo Gómez; María Muñoz; Juan M. García-Casco; Yolanda Nuñez; Rosa Escudero; Ana Heras Molina; Antonio González-Bulnes; Cristina Óvilo; Clemente López-Bote; Ana I. Rey (MDPI AG, 2023)
Modifying the composition of a sow's milk could be a strategy to improve the intestinal health and growth of her piglet during the first weeks of life. This study evaluated how dietary supplementation of vitamin E (VE), hydroxytyrosol (HXT) or VE+HXT given to Iberian sows from late gestation affected the colostrum and milk composition, lipid stability and their relationship with the piglet's oxidative status. Colostrum from VE-supplemented sows had greater C18:1n−7 than non-supplemented sows, whereas HXT increased polyunsaturated (∑PUFAs), ∑n−6 and ∑n−3 fatty acids. In 7-day milk, the main effects were induced by VE supplementation that decreased ∑PUFAs, ∑n−6 and ∑n−3 and increased the Δ-6-desaturase activity. The VE+HXT supplementation resulted in lower desaturase capacity in 20-day milk. Positive correlations were observed between the estimated mean milk energy output and the desaturation capacity of sows. The lowest concentration of malondialdehyde (MDA) in milk was observed in VE-supplemented groups, whereas HXT supplementation increased oxidation. Milk lipid oxidation was negatively correlated with the sow's plasma oxidative status and to a great extent with the oxidative status of piglets after weaning. Maternal VE supplementation produced a more beneficial milk composition to improve the oxidative status of piglets, which could promote gut health and piglet growth during the first weeks, but more research is needed to clarify this.